Biodiesel from Mustard oil: a Sustainable Engine Fuel Substitute for Bangladesh - M.M. Alam; K.A. Rahman (International Journal of Renewable Energy Development, 2013)
Various attractive features of mustard oil based biodiesel as a potential substitute for engine fuel are investigated in this paper for use in Bangladesh. Although the use of mustard oil as edible oil has been reduced, Bangladesh still produces 0.22 million metric tons of mustard oil per year. This surplus mustard oil would satisfactorily be used as an alternative to diesel fuel, and thus could contribute in reducing the expenses for importing fuel from foreign countries. Moreover, the rural people of Bangladesh are capable of producing mustard oil themselves using indigenous machines. Fuel properties of biodiesel obtained from mustard oil were determined in the laboratory using standard procedure and an experimental setup was constructed to study the performance of a small diesel engine. It is observed that with biodiesel, the engine is capable of running without difficulty. Initially different lower blends of biodiesel (e.g., B20, B30 etc.) have been used to avoid complicated modification of the engine and the fuel supply system. It is also found in some condition that mustard oil based biodiesel have better properties than those made from other vegetable oils. These properties of mustard oil based biodiesel were evaluated to validate its sustainability in Bangladesh.